2017
DOI: 10.1088/1361-6439/aa703b
|View full text |Cite|
|
Sign up to set email alerts
|

The negative-differential-resistance (NDR) mechanism of a hydroelastic microfluidic oscillator

Abstract: A microfluidic oscillator is of interest because it converts a stable laminar flow to oscillatory flow, especially in view of the fact that turbulence is typically absent in miniaturized fluidic devices. One important design approach is to utilize hydroelastic effect-induced autonomous oscillations to modify the flow, so to reduce the reliance on external controllers. However, as complex fluid-structure interactions are involved, the prediction of its mechanism is rather challenging. Here, we present a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Notably, we have shown that the framework is programmable, capable of encoding essentially any pressure-drop versus flowrate characteristic in a few simple components. This represents a potential future advance in flow control technology, complementary to existing devices [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we have shown that the framework is programmable, capable of encoding essentially any pressure-drop versus flowrate characteristic in a few simple components. This represents a potential future advance in flow control technology, complementary to existing devices [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The average flow rate and oscillation frequency depend on its geometric structure, elasticity of the diaphragm, the fluid viscosity, and the operating pressure. For a more detailed description of the microfluidic oscillator, please refer to our previous articles. …”
Section: Design and Fabrication Of The Combinatorial Microfluidic Pla...mentioning
confidence: 99%
“…In this work, we propose a combinatorial microfluidic platform consisting of a microfluidic oscillator and a microchip reactor for preparation and screening of nanoscale single-compound and composite explosives. The microfluidic oscillator is based on our previous works, which can convert a stable laminar flow to an oscillatory flow. The microchip reactor with a circular chamber was designed to extend the applicable flow rate range of the microfluidic oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of multiphase flow, such as micro bubbles [ 29 , 30 ]/droplets [ 31 ] and electrochemistry [ 32 ] for microfluidic control are complex in channel fabrication and lack stability or repeatability. Recently, a hydroelastic microfluidic oscillator [ 33 , 34 ], which uses an elastic diaphragm (silicone rubber) as the intermediate layer of the channel, was realized within a medium range of Re (~10–100). Similarly, a microfluidic oscillator was achieved from a channel with two valves made from an elastomeric membrane [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%